New archaeological excavations in the Ca’ Granda Cemetery in Milan: 2019-2021 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
The new archaeological excavations in the Ca’ Granda Cemetery in Milan concerned one of the fourteen sepulchral chambers located under the Church of Beata Vergine Annunciata. The excavation of a small part of the deposit, applying the stratigraphic method, has highlighted a complex situation, characterized by the presence of partially or entirely articulated skeletonised bodies. This condition testifies that the crypt was a primary site of deposition.
Keywords: Ca’ Granda; Milan; sepulchral chambers; stratigraphy; XVII Century